Alveolar recruitment maneuver attenuates extravascular lung water in acute respiratory distress syndrome. Issue 30 (July 2017) - Chung, Fu-Tsai; Lee, Chung-Shu; Lin, Shu-Min; Kuo, Chih-Hsi; Wang, Tsai-Yu; Fang, Yueh-Fu; Hsieh, Meng-Heng; Chen, Hao-Cheng; Lin, Horng-Chyuan
Abstract: Background: The alveolar recruitment maneuver (RM) has been reported to improve oxygenation in acute respiratory distress syndrome (ARDS) and may be related to reduced extravascular lung water (EVLW) in animals. This study was designed to investigate the effects of RM on EVLW in patients with ARDS. Methods: An open label, prospective, randomized controlled trial including patients with ARDS was conducted in hospitals in North Taiwan between 2010 and 2016. The patients were divided into 2 groups (with and without RM). The primary endpoint was the comparison of the EVLW index between the 2 groups. Results: Twenty-four patients with ARDS on mechanical ventilator support were randomized to receive ventilator treatment with RM (RM group, n = 12) or without RM (non-RM group, n = 12). Baseline demographic characteristics were similar between the 2 groups. After recruitment, the day 3 extravascular lung water index (EVLWI) (25.3 ± 9.3 vs 15.5 ± 7.3 mL/kg, P = .008) and the arterial oxygen tension/fractional inspired oxygen ratio (PaO2 /FiO2 ) (132.3 ± 43.5 vs 185.6 ± 38.8 mL/kg, P = .003) both improved over that of day 1. However, both EVLWI and PaO2 /FiO2 did not significantly change from day 1 to 3 in the non-RM group. Conclusion: RM is a feasible method for improving oxygenation and the EVLW index in patients with ARDS, as well as for decreasing ventilator days and intensive care unit stay duration.